Segregación de funciones en el Multicomercio Don Saúl ubicado en la ciudad de Babahoyo, período 2022. - Apraez Montero, Ximena Noeli (2023)
The development of the investigation carried out within the Multicomercio "Don Saúl", to make known what refers to the segregation of functions established in the organization, aims to evaluate the variable and identify how it can affect the efficiency, the degree of compliance with the tasks of the staff, in addition to business growth and therefore in the perception of customers; demostrando la importancia de la ejecución del estudio, puesto que la variable expuesta se considera relevante en el desarrollo interno de todas las empresas, ya que al no existir una distribución adecuada de las actividades, se desencadenan situaciones negativas como duplicidad de trabajo, desorganización, improductividad por parte de cada uno de los trabajadores, que a su vez conlleva, dificultad en la consecución de los objetivos a corto y largo plazo. The investigative tools used to obtain relevant information from the study, was the interview directed to the administrative staff of the multi-store and also a survey directed to the citizens of the city of Babahoyo who are the potential clients of the company under analysis. The data collection showed as a result that the level of efficiency is low, that there are no professional and systematized management models, in addition to the lack of controls and evaluations to know the performance of each one of the workers, and as an important aspect, the non-existence of a functions manual that allows the correct distribution of tasks according to the needs of each area.